ANALISIS KEPUASAN PELANGGAN PDAM TIRTA MERAPI KABUPATEN KLATEN TAHUN 2022 - Nursito, Sarwono; Nugroho, Arif Julianto Sri; Haris, Abdul (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2022)
This study aims to determine the index of the Customer Satisfaction Survey (SKP) of public services provided by the Regional Water Company (PDAM) Tirta Merapi Klaten Regency in 2022. The method used in this study was a survey using a questionnaire to collect research data. The sample of this research is 400 customers. The sampling technique uses cluster and stratified sampling. Data analysis in this study uses the analysis of the Customer Satisfaction Survey Index (SKP). The analysis of the SKP index is carried out as a whole and per service element. The results obtained indicate that the index value of the Customer Satisfaction Survey (SKP) is 77.05. These results show that the service quality of PDAM Tirta Merapi Klaten Regency in 2022 is in category B, which means it has good service performance. In addition, the results of the SKP index analysis per service element, consisting of 9 service elements, show good service performance.